Environmental Education in the work of the National Chemistry Teaching Meeting (Research, Society and Development, 2021)
This article sought to investigate and draw a profile of how Environmental Education (EE) has been addressed in the teaching of chemistry. For this, 64 full papers obtained from the search in free directories that make up the annals of the National Meeting on Teaching of Chemistry(ENEQ) published in 5 (five) editions of the event from 2010 to 2018 were analyzed. The methodology had a qualitative approach and used document analysis with a focus on Systematic Literature Review (RSL). Bardin's Content Analysis technique was applied to assess the data collected, As a result, a growth in the production of works related to EA over the years that may have been driven by exponentially in the forms and means of dissemination and demonstrate an overview of the existence of various approaches, methodologies and references addressed at different levels and segments of basic education, higher education and communities. In conclusion, we realize that EA, when linked to the teaching of chemistry, still needs research and dissemination of teaching practices that address Environmental Education in its multiple dimensions.